Pancreatic adenocarcinoma with primary tumor calcification and calcified liver metastasis: Report of a rare case and review of literature - Joydeep Ghosh; Sandip Ganguly; Deepak Dabkara; Bivas Biswas; Arghya Chatterjee; Sumit Mukhopadhyay; Sudeep Banerjee; Saugata Sen; Indu Arun (Indian Journal of Medical and Paediatric Oncology)
Calcification is a feature of benign pancreatic diseases such as chronic calcific pancreatitis (CCP) or benign pancreatic tumors such as solid and papillary epithelial neoplasm of the pancreas and serous cystadenoma. The presence of calcification in a primary malignant pancreatic tumor is uncommon except for neuroendocrine tumors of the pancreas. Calcification in adenocarcinoma of the pancreas involving the primary tumor as well as the metastasis resulting thereof is extremely rare in the absence of CCP. To our knowledge, this is the first report of a case of primary adenocarcinoma of the pancreas that presented with calcification of the primary tumor as well as the metastatic liver nodules, accompanied by hypercalcemia.